FACTORS AFFECTING THE TRANSFER OF USE OF MARKS HANDPHONE AMONG THE STUDENTS Case study of University Students Mercu Buana Yogyakarta - Gandaria, Denok; Lastari, SE., MM., Siwi; Darini, M.Si., Dra. Sri (Management, 2010)
This research focused to know what factors are affecting the movement of mobile phone brands use among students at the University Mercu Buana Yogyakarta. In addition, this study also aims to determine why students are choosing a particular brand of mobile phones as a communication tool, find the displacement using a mobile phone brand to another brand, make projections of the global handset market share among the students of the University of Mercu Buana Yogyakarta. Methods of data collection in this research is the questionnaire method by using Likert scale. To predict the market share of each brand of mobile phone use Markov Chain analysis, so that the resulting market share of Nokia in 2008 by 49%, 19% S. Ericsson, Motorola 10%, Samsung at 8%, Siemens 11%, and LG 3%. In 2009 Nokia market share of 51%, 18% S. Ericsson, Motorola 9%, 9% Samsung, Siemens 8%, and LG 6%. Year 2010 Nokia market share of 50%, 18% S. Ericsson, Motorola 9%, 8% Samsung, Siemens 7%, and LG 9%. Nokia 2011 market share of 49%, 17% S. Ericsson, Motorola 8%, 8% Samsung, Siemens 7%, and LG 12%. Multiple linear regression analysis used to determine the influence of external factors which consist of the price (X1), feature (X2), design (X3), durability (X4) and ease of operation (X5) to transfer the use of mobile phone brands among college students (Y). Data analysis was performed with the aid of SPSS 12.0 for Windows software aimlessly following regression equation: Y = 3.397 + 0.237 X1 + 0.270 X2 + 0.208 X3 + 0.335 X4 + .210 X5 Based on the above equation can be seen that the variable pricing, features, design, durability, and ease of operation have a positive influence on movement of the use of mobile phone brands among. Keywords: Projections, Market Share. college students.